Advances in Microfluidic Cochlea‐On‐A‐Chip - Tian Shen; Shanying Han; Weiwei He; Wen Yang; Xinghua Tang; Xiaolong Zhao; Xinghong Liu; Zhenhua Shao; Lin Cheng; Yu Zhao; Jiangang Fan (Advanced Science)
Abstract The current understanding of the human auditory system has been primarily based on studies using animal and cellular models. Organoids have been used to simulate cochlear structures and replicate cochlear functions. However, the physical and chemical cues required to control the development of cochlear organoids accurately remain poorly understood, limiting research advances on cochlea‐on‐a‐chip systems. Consequently, the development of cochlea‐on‐a‐chip platforms that provide reliable preclinical testing grounds for studying inner ear developmental mechanisms and screening‐related therapeutic drugs has become a key focus for future cochlea‐on‐a‐chip technologies. In this review, the recent advancements in cochlea‐on‐a‐chip technology are summarized. First, an overview of cochlear anatomy and physiology is provided. Next, the latest breakthroughs are discussed in the 3D cultivation of inner ear organoids and explore the progress in microfluidic technologies for constructing cochlea‐on‐a‐chip systems. Finally, perspectives are presented on the current challenges and future directions for developing cochlea‐on‐a‐chip technology.